La supervisión técnica en proyectos de construcción de edificaciones según la normativa sismo resistente colombiana (2020)
The collapse of the Space building had to happen in October 2013, to make visible the need to reinforce the rules, strengthen their application and confer new responsibilities on public and private institutions committed to the activities of construction and disposal of housing. With the issuance by the Presidency of the Republic of Law 1796 of 2016, it obliges all builders to carry out Technical Supervision in projects of buildings larger than 2,000 m2, who will be responsible for issuing the Technical Certificate of Occupation to the finish the work, as a guarantee to the end-user that the work was carried out under Colombian technical standards.